2017
DOI: 10.1371/journal.pone.0188403
|View full text |Cite
|
Sign up to set email alerts
|

The peer review gap: A longitudinal case study of gendered publishing and occupational patterns in a female-rich discipline, Western North America (1974–2016)

Abstract: Researchers have repeatedly demonstrated that women continue to be underrepresented in publication output in the sciences. This is true even in female-rich fields such as archaeology. Since most gender-related publication studies rely on data from peer-reviewed journals, it would be instructive, though challenging, to also track publication output in non-refereed and professional or industry venues, which tend to be more accessible to those working in extra-academic settings. This comparison is important in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 34 publications
3
39
0
Order By: Relevance
“…Clearly, women's participation rates have grown historically and today account for more than half of all PhDs earned and are approaching parity among SAA memberships and RPA registrants. These trends parallel membership findings at the regional level, where women now represent half or more of members of the Society for California Archaeology (Tushingham et al 2017:Figure 2).
Figure 1.Annual percentage representation of women PhD graduates, Register of Professional Archaeologists (RPA) and Society of Professional Archaeologists (SOPA) members/registrants, and Society for American Archaeology (SAA) members in the United States from as early as 1967 to 2018.
Figure 2.Longitudinal trends in the percentage of women lead authors from three regional archaeology journals published from 2000 to 2017.
…”
Section: Sociopolitics Demographic Landscapes and The “Leaky Pipelisupporting
confidence: 70%
See 1 more Smart Citation
“…Clearly, women's participation rates have grown historically and today account for more than half of all PhDs earned and are approaching parity among SAA memberships and RPA registrants. These trends parallel membership findings at the regional level, where women now represent half or more of members of the Society for California Archaeology (Tushingham et al 2017:Figure 2).
Figure 1.Annual percentage representation of women PhD graduates, Register of Professional Archaeologists (RPA) and Society of Professional Archaeologists (SOPA) members/registrants, and Society for American Archaeology (SAA) members in the United States from as early as 1967 to 2018.
Figure 2.Longitudinal trends in the percentage of women lead authors from three regional archaeology journals published from 2000 to 2017.
…”
Section: Sociopolitics Demographic Landscapes and The “Leaky Pipelisupporting
confidence: 70%
“…Early inquiries into the representation of women in peer-reviewed publishing demonstrated that throughout the twentieth century, the climate of archaeology had remained “quite chilly” for women, with a lack of gender parity in published articles, reviewer demographics, and citation practices (Beaudry 1994; Beaudry and White 1994; Victor and Beaudry 1992:16–17; see also Hutson 2002). Gender imbalances exist regionally and nationally (Bardolph 2014, 2018; Bardolph and VanDerwarker 2016; Claassen et al 1999; Tushingham et al 2017), despite the strong representation of women practitioners in archaeology. Authorship imbalances exist not only in academic journals but also in popular-culture archaeology magazines that communicate our discipline to the public (e.g., Colwell-Chanthaphonh 2004).…”
Section: Sociopolitics Demographic Landscapes and The “Leaky Pipelimentioning
confidence: 99%
“…Since the 1980s, activist archaeologists have been criticizing the lack of diversity in the profession of archaeology. This has come most commonly in the form of gender equity publications, in which scholars assign masculine or feminine identifications to journal-article authors or grant recipients in order to quantify men's domination in the discipline (e.g., Bardolph 2014, 2018; Bardolph and Vanderwarker 2016; Beaudry and White 1994; Ford 1994; Ford and Hundt 1994; Fulkerson and Tushingham 2019; Gero 1985; Goldstein et al 2018; Hutson 2002; Rautman 2012; Tushingham et al 2017; Victor and Beaudry 1992; Yellen 1991). The most recent Society for American Archaeology (SAA) Needs Assessment Survey (Association Research 2016:5), which was conducted in 2015, demonstrated that the membership of the organization is approaching gender parity, with 50.5% of respondents being male, 47.9% being female, 0.2% being of another gender, and 1.3% preferring not to answer.…”
Section: Demography Of the Fieldmentioning
confidence: 99%
“…(Tamblyn, Girard, Qian, & Hanley, 2018), that we are subject to conscious and unconscious biases (Fay, 1993;Steinpreis, Anders, & Ritzke, 1999). The evidence on bias in peer review is mixed, with some studies concluding that bias occurs (Link, 1998;Tomkins, Zhang, & Heavlin, 2017;Tushingham, Fulkerson, & Hill, 2017), and other studies finding no significant impact (Lee, 2012), for example, Burns and Fox (2017) concluded that socioeconomics and language are more important factors than editor or reviewer bias in explaining geographic variation in acceptance rates ; and see also Engqvist & Frommen, 2008). Authorsuggested reviewers have been found to be more favourable than editor-selected reviewers (Bornmann & Daniel, 2010;Fox, Burns, Muncy, Meyer, & Thompson, 2017).…”
Section: F4 -Confidentialitymentioning
confidence: 99%